226k views
2 votes
Arnoldo needs to write this system in slope-intercept form. Which shows how he could do that? 3 x minus 2 y = 6. 0.4 (20 y + 15) = x. y = negative three-halves x + 3 y = one-eighth x minus three-fourths y = three-halves x minus 3 y = one-eighth x minus three-fourths y = negative three-halves x minus 3 y = one-fifth x minus StartFraction 15 Over 4 EndFraction y = three-halves x minus 3 y = one-fifth x minus StartFraction 15 Over 4 EndFraction

2 Answers

4 votes

Answer:

The slope intercept form of 3x - 2y = 6 is
y = (3x)/(2) - 3

In other words, y = three-halves x minus 3

Explanation:

Given:

3x - 2y = 6

Required:

Proper representation of the slope intercept form

To get the proper system that represents the given expression, we have to make y the subject of the formula.

Follow the steps below

Step 1: Write out the expression

3x - 2y = 6

Step 2: Take 3x to the other side of the equation

- 2y = 6 - 3x

Step 3: Multiply both sides by -1

-1 * -2y = -1 * (6 - 3x)

Step 4: Write out result

2y = 3x - 6

Step 5: Divide both sides by 2


(2y)/(2) = (3x - 6)/(2)


y = (3x - 6)/(2)

Step 6: Split fraction


y = (3x)/(2) - (6)/(2)


y = (3x)/(2) - 3

Hence, the slope intercept form of 3x - 2y = 6 is
y = (3x)/(2) - 3

In other words, y = three-halves x minus 3

User SNash
by
4.9k points
4 votes

Answer:

y = three-halves x minus 3

Explanation:

Subtract 3x from both sides of the original equation.

-2y = -3x +6

Divide by -2

y = 3/2x -3

User Yvan
by
4.4k points